Faktor yang Berhubungan dengan Kejadian Berat Badan Lahir Rendah (BBLR) di RS Cikarang Medika Tahun 2021: Factors Associated with Low Birth Weight (LBW) at Cikarang Medika Hospital in 2021 - Anggun Sri Bintang; Eti Salafas (Journal of Holistics and Health Sciences (JHHS), 2022)
Low Birth Weight (LBW) is a baby born weighing less than 2500 grams regardless of gestational age. LBW is still a major public health problem, it is estimated that 15-20% of all births worldwide are LBW which represents more than 20 million births per year. The purpose of this study was to determine the factors associated with the incidence of LBW in Cikarang Medika Hospital in 2021. This study used descriptive analytic with a cross sectional approach. The study population was all women who gave birth at Cikarang Medika Hospital with a total population of 439 respondents, using secondary data. Bivariate analysis using chi square with 5% obtained p value of maternal age = 0.000 and OR = 102.734 (95% CI 53.178 - 198.470), parity = 0.000 and OR = 61.967 (95% CI 33.999 - 112.940), gestational interval = 0.000 and OR = 169.650 (95% CI 81.656 – 352.4677), HB level = 0.000 and OR = 272.779 (95% CI 120.947 – 615.215). The conclusion is that there is a relationship between maternal age, parity, gestational distance, and HB levels with the incidence of Low Birth Weight at Cikarang Medika Hospital in 2021. It is expected that pregnant women are of healthy reproductive age, namely 20-30 years, limiting the number of children to 2 children with a minimum distance of pregnancy. 3 years. It is expected that routine ANC so that Hb levels can be monitored and Fe tablet supplements are met, thus it is hoped that babies born have normal weight ABSTRAK BBLR adalah bayi lahir dengan berat badan kurang dari 2500 gram tanpa memandang masa kehamilan. BBLR sampai saat ini masih menjadi masalah kesehatan masyarakat yang utama, diperkirakan 15-20% dari semua kelahiran di seluruh dunia adalah BBLR yang mewakili lebih dari 20 juta kelahiran per tahun. Tujuan penelitian ini untuk mengetahui faktor-faktor yang berhubungan dengan kejadian BBLR di RS Cikarang Medika Tahun 2021. Penelitian ini menggunakan deskriptif analitik dengan pendekatan cross sectional. Populasi penelitian adalah seluruh wanita yang melahirkan di RS Cikarang Medika dengan jumlah populasi sebanyak 439 responden, menggunakan data sekunder. Analisa bivariate menggunakan chi square dengan α 5% diperoleh p value hubungan usia ibu = 0,000 dan OR = 102,734 (95% CI 53,178 – 198,470), paritas = 0,000 dan OR = 61,967 (95% CI 33,999 – 112,940), jarak kehamilan = 0,000 dan OR = 169,650 (95% CI 81,656 – 352,4677), Kadar HB = 0,000 dan OR = 272,779 (95% CI 120,947 – 615,215). Kesimpulan terdapat hubungan antara usia ibu, paritas, jarak kehamilan, dan kadar HB dengan kejadian Berat Badan Lahir Rendah di RS Cikarang Medika Tahun 2021. Diharapkan ibu hamil diusia reproduksi sehat yaitu 20 – 30 tahun, membatasi jumlah anak 2 anak cukup dengan jarak hamil minimal 3 tahun. Diharapkan rutin ANC sehingga kadar Hb dapat terpantau dan suplemen tablet Fe terpenuhi, dengan demikian diharapkan bayi yang dilahirkan beratnya normal.